Regressions to Monitor Health Care Quality: A User’s Guide and a New Index - Butler, Richard J.; Johnson, William G. (International Journal of Statistics in Medical Research, 2012)
: While there is a rich literature regarding hospital quality in general, research examining trends in hospital quality using regression analysis of trends are relatively rare. In the presence of the increasing digitalization of hospital data, the wide accessibility of regression software, and the need for real time feedback on ongoing quality of medical care outcomes, this paper presents simple-to-implement techniques for analyzing the quality of health care outcomes. We present graphical illustrations of the techniques discussed, and we also include a SAS appendix with the code to estimate all the models discussed, including a proposed new regression index: the Exchange index. We employ data from Arizona’s acute care hospitals to illustrate uses of our new index.